Analysis of Organizational Commitment and Work Discipline on Employee Performance Using Work Environment as an Intervening Variable at PT. YKT Gear Indonesia During the Covid-19 Pandemic - Pipin Eka Apriani; Masydzulhak Djamil (Dinasti Publisher, 2023)
The purpose of this study is to analyze the effect of organizational commitment, work discipline and work environment on performance and formulate strategies to improve performance during the Covid-19 pandemic by taking case studies at PT. YKT Gear Indonesia. a quantitative descriptive research design was used by the authors in 260 participants made up the sample of 160 respondents for survey. The Partial Least Squares approach is an analysis technique (PLS), Research results prove that (1) Organizational Commitment influences the work environment positively and significantly (2) Workplace environment is significantly and favorably affected by work discipline (3) Organizational commitment influences employee performance positively and significantly (4) Employee performance is positively and significantly impacted by work discipline. (5) Employee performance is positively and significantly influenced by the work environment (6) Organizational Commitment has a positively and significantly effect on employee performance through the work environment as an intervening variable (7) Employee performance is positively and significantly influenced by work discipline through the work environment. Suggestions and input for PT. YKT Gear Indonesia to be committed and paying attention to the workplace environment to encourage more discipline among staff, and can carry out their duties and obligations properly.